Pediatric Traumatic Retinal Detachment: Clinical Features, Prognostic Factors, and Surgical Outcomes - Dilek Yaşa; Zeynep Gizem Erdem; Ufuk Ürdem; Gökhan Demir; Ali Demircan; Zeynep Alkın (Journal of Ophthalmology)
Purpose. We report the clinical characteristics, prognostic factors, and surgical outcomes for 23-gauge pars plana vitrectomy (23-G PPV) in pediatric cases of traumatic retinal detachment (RD). Methods. Medical records of pediatric patients who underwent 23-G PPV to treat traumatic retinal detachment were retrospectively reviewed. These patients underwent a follow-up examination at least 1 year following surgery. Associations between various preoperative factors and anatomical and visual outcomes were analyzed. An Ocular Trauma Score (OTS) and a Pediatric Ocular Trauma Score (POTS) were calculated for each patient. Raw scores were converted to their corresponding OTS and POTS categories. Final visual acuities by categories were compared with those in the OTS and POTS studies. Results. The mean age of the patients was 9 ± 4 years, and the male-to-female ratio was 4.7 : 1. The mean follow-up time was 23 ± 14 months. Anatomical success was achieved in 72% of the eyes, and functional success (>5/200) was achieved in 37% of the eyes. Functional success was less common among patients with visual acuities less than hand motion, macula-off retinal detachment, proliferative vitreoretinopathy at presentation, and recurrent retinal detachment during follow-up. When we compared the categorical distribution of final visual acuities in all categories, our results were significantly different than those suggested by OTS and POTS. Conclusions. Visual outcomes are poorer compared to anatomical outcomes. OTS and POTS do not provide reliable prognostic information if the patient has RD. Presenting visual acuity, the presence of macula-off RD, and PVR are all important predictors of final visual acuity.